Beating the Covid-19 blues with dance and songs: women's group work in the times of a pandemic. Issue 1 (2nd January 2022) - Nancy,
ABSTRACT: While the coronavirus has brought the world to a standstill; the lives of women have become even more hectic. Since the nationwide lockdown in India, a multitude of factors – fear, uncertainty, isolation, increased care work, domestic violence, and lack of peer support had started taking a toll on a group of women in New Delhi. Soon, their group – Gopi Mahila Mandal intervened, providing these women from low socio-economic backgrounds a unique platform to navigate through the crisis. In these uncertain times, when the whole world is anxious, the women of Gopi Mahila Mandal are celebrating. Through their songs and dance, they are spreading joy in their lives and beating the covid-19 blues.